2023
DOI: 10.1101/2023.02.23.529726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Gulf Stream frontal eddy harbors a distinct microbiome compared to adjacent waters

Abstract: Marine microbiome community assembly and consequently biogeochemical cycling are shaped by past and current environments, as well as stochasticity, dispersal etc. To better understand the processes that structure marine microbial communities, we examine a cyclonic, Gulf Stream frontal eddy, whose microbiome potentially contains signatures of both the shelf community entrained during formation as well as current environmental conditions. In spite of the potential for eddy-driven upwelling to introduce nutrients… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…A companion study (Gronniger et al 2023), focused on the eddy microbiome, was undertaken on the same flow-through surface samples and similarly reveals differences in microbial community composition between water masses. Although samples were categorized differently, Gronniger et al (2023) found that the eddy harbored higher abundance of Prochlorococcus and lower abundances of Synechococcus and Pelagibacteraceae . However, despite differences between the Gulf Stream and eddy microbiomes, including higher abundances of Prochlorococcus in the eddy and higher abundances of the nitrogen-fixer Trichodesmium in the Gulf Stream (see also Figure 6), the eddy is most similar to the Gulf Stream relative to the other water masses, suggesting that assembly of the eddy microbiome is primarily determined by environmental filtering in these warm, low nutrient waters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A companion study (Gronniger et al 2023), focused on the eddy microbiome, was undertaken on the same flow-through surface samples and similarly reveals differences in microbial community composition between water masses. Although samples were categorized differently, Gronniger et al (2023) found that the eddy harbored higher abundance of Prochlorococcus and lower abundances of Synechococcus and Pelagibacteraceae . However, despite differences between the Gulf Stream and eddy microbiomes, including higher abundances of Prochlorococcus in the eddy and higher abundances of the nitrogen-fixer Trichodesmium in the Gulf Stream (see also Figure 6), the eddy is most similar to the Gulf Stream relative to the other water masses, suggesting that assembly of the eddy microbiome is primarily determined by environmental filtering in these warm, low nutrient waters.…”
Section: Discussionmentioning
confidence: 99%
“…A companion study (Gronniger et al, 2023), focused on the eddy microbiome, was undertaken on the same flow-through surface samples and similarly reveals differences in microbial community composition between water masses. This companion study found that the eddy harbored higher abundance of Prochlorococcus and lower abundances of Synechococcus and Pelagibacteraceae .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations